Comparative Genome Analysis and Phenotypic Characterization of Clostridium gasigenes CGAS001 Isolated From Chilled Vacuum-Packed Lamb Meat - Wambui, Joseph; Cernela, Nicole; Corti, Sabrina; Stephan, Roger (Frontiers in Microbiology, 2020)
Genomic data for psychrophilic bacteria causing blown pack spoilage (BPS) are limited. This study characterizes the genome of a novel Clostridium gasigenes strain CGAS001 isolated from meat juice sample (MJS) of vacuum-packed lamb meat by comparing it with the type strain C. gasigenes DSM 12272 and five strains representing four other BPS-causing Clostridium sensu stricto species. Phenotypic characteristics of the strain, which include biochemical characteristics, antimicrobial resistance and production of putative polyketide, have been determined. The strain has also been characterized phenotypically. The size of its draft genome is 4.1 Mb with 3,845 coding sequences, 28.7% GC content and 95 RNA genes that include 75 tRNAs, 17 rRNAs and 3 ncRNAs. Average Nucleotide Identity (ANI) and digital DNA-DNA Hybridization (dDDH) predict that C. gasigenes CGAS001 and DSM 12272 constitute a single species (ANI and dDDH = 98.3% for speciation) but two distinct subspecies (dDDH = 73.3% for subspeciation). The genome is characterized by saccharolytic, lipolytic and proteolytic genes as well as hemolysins and phospholipases, which are consistent with its phenotype. The genome also reveals the ability of C. gasigenes to synthesize polyketides which is demonstrated by the antimicrobial activity of a crude polyketide extract against Listeria monocytogenes and Enterococcus devriesei. The strain is resistant to polymyxin B and streptomycin. The genetic and phenotypic analyses suggest that CGAS001 constitutes a novel subspecies of C. gasigenes adapted to a saprophytic lifestyle and can synthesize narrow spectrum antimicrobial compounds.